On ‘Rusting’ Money: Silvio Gesell’s Schwundgeld Reconsidered. Part II: The Long Run - Rehme, Günther (Review of Economic Analysis, 2024)
Silvio Gesell argued that ‘rusting’ money is economically and socially beneficial; that claim has often been contended. In Part II of the paper, I concentrate on the long-run implications of his ideas. I show that introducing money depreciation in isolation may be economically non-beneficial in typical long-run equilibrium. But money depreciation, when coupled with expansionary monetary policy, is a necessary condition for a positive Mundell-Tobin effect on long-run real variables and so creates wealth in the model. It is found that this also holds in the transition to the long-run equilibrium. Hence, the spirit of Gesell’s hypotheses can be verified for a plausible, long-run environment as well, and may, thus, be relevant for long-run economic policy problems.